Evaluation of flax varieties of the long-lived Tomsk breeding in the CRNZ - Simagin A.D.; Simagina A.S.; Barnashova E.K.; Vertikova E.A.; Pokrovskaya D.A. (BIO Web of Conferences)
In 2024, 6 varieties of the Tomsk school of breeding were tested at the RGAU MSHA field experimental station. the conditions of the year for the cultivation of flax proved to be optimal. Among all varieties, the Tomich variety was distinguished by the highest fiber yield (36.5%). In terms of seed productivity, the Tomsk 18 variety was the leader (82.5 pieces per plant), however, the same variety showed the lowest safety for harvesting (420 plants from 1 plot). The Krepkov Memory variety had the highest technical length (71.28 cm).